MODEL PEMANTAUAN ALIRAN AIR SUNGAI DAN CURAH HUJAN BERBASIS JARINGAN SENSOR NIRKABEL - , IHYAUDDIN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
One cause of floods is heavy rainfall which is occurred and the extent of the rivers which are no longer able to accommodate the flow of water. Floatation of river occurs unpredictable could not be detected by flood gates officer or suburban population who live on the river side area. Device is expected to provide information about river flow condition and rainfall which is occurred. This research explained design and implementation of the river flow monitoring model based on wireless sensor networks. The model applied two nodes to measure water level, rainfall, speed of flow, and power source. The microcontroller as a processor will collect sensor sampling result then form it to be a data packet. Those would be sent to the fusion center through wireless media. The node has collected sensor sampling. The information about river flow condition has been displayed by fusion center. Rainfall can be measured per 5.492 ml. Average error of flow measurement is 14%. Successful inter-node communication is done using baudrate 9600 bps.